Integrated assessment of epidemic and economic dynamics - Oliver Holtemöller (Halle Institute for Economic Research (IWH), 2020)
In this paper, a simple integrated model for the joint assessment of epidemic and economic dynamics is developed. The model can be used to discuss mitigation policies like shutdown and testing. Since epidemics cause output losses due to a reduced labor force, temporarily reducing economic activity in order to prevent future losses can be welfare enhancing. Mitigation policies help to keep the number of people requiring intensive medical care below the capacity of the health system. The optimal policy is a mixture of temporary partial shutdown and intensive testing and isolation of infectious persons for an extended period of time.
urn:nbn:de:gbv:3:2-119677
Keywords: E1; H0; I1; 330; coronavirus; economic growth; epidemic modeling